2020
DOI: 10.3390/ijms21197232
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-31 Regulates Expression of Wntless in Both Drosophila melanogaster and Human Oral Cancer Cells

Abstract: Recent comparative studies have indicated distinct expression profiles of short, non-coding microRNAs (miRNAs) in various types of cancer, including oral squamous cell carcinoma (OSCC). In this study, we employed a hybrid approach using Drosophila melanogaster as well as OSCC cell lines to validate putative targets of oral cancer-related miRNAs both in vivo and in vitro. Following overexpression of Drosophila miR-31, we found a significant decrease in the size of the imaginal wing discs and downregulation of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 97 publications
0
5
0
Order By: Relevance
“…In addition, miR‐31 passenger strand regulates RhoA (Ras homolog family member A gene) expression, which leads to proliferation and migration of oral cancer cells (Chang et al, 2013). Proliferation and cell cycle of oral cancer cells is regulated by miR‐31 and its regulation of cyclin D1, c‐myc and WLS , important for Wnt signalling (Jung et al, 2020). As a putative target of miR‐31 in head and neck carcinoma was also identified NUMB gene, through which migration and invasion of cancer cells are facilitated (Chou et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, miR‐31 passenger strand regulates RhoA (Ras homolog family member A gene) expression, which leads to proliferation and migration of oral cancer cells (Chang et al, 2013). Proliferation and cell cycle of oral cancer cells is regulated by miR‐31 and its regulation of cyclin D1, c‐myc and WLS , important for Wnt signalling (Jung et al, 2020). As a putative target of miR‐31 in head and neck carcinoma was also identified NUMB gene, through which migration and invasion of cancer cells are facilitated (Chou et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“… 20 Recently, in vitro studies have suggested a potential role of miR-31 in regulating cell cycle and proliferation of OSCC tissues via Wnt and Hippo signalling pathways. 21 , 22 …”
Section: Discussionmentioning
confidence: 99%
“…The potential targets of miR-31 were studied by Jung JE et al. ( 76 ), in Drosophila melanogaster and OSCC cell line models. The study confirmed the association of miR-31 in the maintenance of human Wntless mRNA, which is a key regulator of Wnt signaling.…”
Section: Intrinsic Factors Governing Oscc Stemnessmentioning
confidence: 99%